Jews, Gentiles, and ethnic reconciliation : Paul's Jewish identity and Ephesians - Yee, Tet-Lim N. (Monograph series (Society for New Testament Studies), 2005)
Much recent scholarship has focused on Paul's insistence on Gentile membership of the people of God equally with Jews. This book contributes to the continuing reassessment of Christian and Jewish self-understanding during the latter decades of the first century and reveals how a distinctively Jewish world view underlies Ephesians 2.